Beta-1, 3-1, 6-glucan modulate the non-specific immune response to enhance the survival in the Vibrio alginolyticus infection of Taiwan abalone (Haliotis diversicolor supertexta). (July 2016) - Wu, Yu-Sheng; Tseng, Tzu-Yu; Nan, Fan-Hua
Abstract: This research aims to investigate the non-specific immune response of Taiwan abalone ( Haliotis diversicolor supertexta ) which was treated with the beta-1, 3-1, 6-glucan to be observed in the survival impact after the Vibrio alginolyticus infection. The non-specific immune and physiological response of superoxide anion radical (O2 − ), phenoloxidase (PO), phagocytic index (PI), phagocytic rate (PR) and lucigenin-chemiluminescence for reactive oxygen intermediates (ROIs) were enhanced via in-vitro experiment. In the in-vivo experiment, the observed data presented that the haemolymph lysate supernatant (HLS), superoxide dismutase (SOD), glutamate oxalacetate transaminase (GOT) and glutamate pyruvate transaminase (GPT) were not significant enhanced, but the total haemocyte count (THC), O2 −, PO, phagocytic index (PI), phagocytic ratio (PR) and other parameters of immune were significantly promoted after treated with beta-1, 3-1, 6-glucan. In the challenge experiment, the survival rates of abalone in the 40 and 80 μl/ml groups of beta-1, 3-1, 6-glucan were observed from 6.67% up to 33.33% and 36.67% after injection with Vibrio alginolyticus, respectively. Highlights: Role of beta-1, 3-1, 6-glucan in inducing the nonspecific immune response of Haliotis diversicolor supertext and its potential applications in pharmaceutical developments. H. diversicolor supertexta injected with beta-1, 3-1, 6-glucan had a higher survival rate than did the control group under Vibrio alginocyticus infection. The total haemocyte count (THC), O2 −, PO, phagocytic index (PI), phagocytic ratio (PR) and other parameters of immune were significantly promoted after treated with beta-1, 3-1, 6-glucan.